Introduction to renewable power systems and the environment with R - Acevedo, Miguel F.; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
This textbook introduces the fundamentals of renewable electrical power systems examining their direct relationships with the environment. It covers conventional power systems and opportunities for increased efficiencies and friendlier environmental interactions. While presenting state-of-the-art technology, the author uses a practical interdisciplinary approach explaining electrical, thermodynamics, and environmental topics within every chapter. This approach allows students to feel comfortable moving across these disciplines. The added value are the examples of software programs using open source systems which serve as learning tools for the concepts and techniques described in the book.
chapter 1 Introduction -- chapter 2 Environmental Systems, the Carbon Cycle, and Fossil Fuels -- chapter 3 Fundamentals of Direct Current Electric Circuits -- chapter 4 Thermodynamics -- chapter 5 Electrical Storage Elements, Basics of AC Circuits, and AC-DC Conversion -- chapter 6 More Thermodynamics State Functions: Entropy, Enthalpy, and Free Energy -- chapter 7 Coal- and Steam-Based Processes -- chapter 8 Alternating Current (AC) Circuits and Power -- chapter 9 Gas and Liquid Fuels: Gas Turbines and Combustion Engines -- chapter 10 Transformers and Three-Phase Circuits -- chapter 11 Power Systems and the Electric Power Grid -- chapter 12 Hydroelectric Power Generation -- chapter 13 Wind Resources and Wind Power -- chapter 14 Solar Power.
Keywords: R (Computer program language); TECHNOLOGY & ENGINEERING / Mechanical; TECHNOLOGY & ENGINEERING / Power Resources / Alternative & Renewable; TECHNOLOGY & ENGINEERING / Power Resources / Electrical; Electric power production -- Data processing; R (Computer program language); Renewable energy sources